Prediction of stocks price movement - Wong, Siew Hong. (2010)
In finance, investors are particularly interested in forecast of financial markets because of its ability to capture and comprehend information of the market, thus instilling investors’ confidence. There are several forms of financial forecasts, namely, Technical Analysis, Quantitative Analysis and Fundamental Analysis. The task of stock forecasting in Technical Analysis divides researchers and academics into two groups who believe that mechanisms can be used to beat the market and those who believe the market is always efficient with no space for prediction, as stated in the strong-form of the Efficient Market Hypothesis. The latter group also believes in the Random Walk principle, which implies that the best prediction value we can have about tomorrow’s value is today’s value. The Efficient Market Hypothesis (EMH), in its weak-form, suggests that future prices of securities cannot be predicted consistently by just analyzing historical prices. However, it does not deny the fact that in the short run, investing strategies such as Technical Analysis can potentially yield excess returns. In general, although Technical Analysis cannot be treated as the best investing tool, it does help investors to identify and suggest trading opportunities.